2019
DOI: 10.1055/s-0039-1693426
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Clinical Decision Support System to Improve Medication Safety

Abstract: Background Clinical decision support systems (CDSSs) are a good strategy for preventing medication errors and reducing the incidence and severity of adverse drug events (ADEs). However, these systems are not very effective and are subject to multiple limitations that prevent their implementation in clinical practice. Objectives The objective of this study was to evaluate the effectiveness of an advanced CDSS, HIGEA, which generates alerts based on predefined clinical rules to identify patients at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…The patients' characteristics were similar between phases, and those with RD (< 60 mL/min/1.73 m 2 ) were one-third of all admitted patients (►Table 2). The median (interquartile range) length of hospital stay was 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) days.…”
Section: Resultsmentioning
confidence: 99%
“…The patients' characteristics were similar between phases, and those with RD (< 60 mL/min/1.73 m 2 ) were one-third of all admitted patients (►Table 2). The median (interquartile range) length of hospital stay was 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) days.…”
Section: Resultsmentioning
confidence: 99%
“…5 Two decades later, EHRs and computerized provider order entry (CPOE) systems have found their way into nearly every hospital and feature computerized clinical decision support (CDS) as a standard. 6,7 A systematic review of medication-related CPOE systems with CDS identified five studies where CDS led to a statistically significant decrease in ADEs, and five studies where there was no significant reduction of ADEs after CDS implementation. 8 In clinical practice, CDS alerts are often overridden or ignored, and potential issues with medication-related CDS are not well understood.…”
Section: Background and Significancementioning
confidence: 99%
“…6 CDS systems, now largely available across healthcare institutions, incorporate various features such as documentation templates, clinical guidelines, diagnostic support, drug alerts, and reminders. [7][8][9][10] The utilization of CDS has demonstrated different advantages for improving practitioner performance and clinical care, including prevention of harmful prescriptions 11 and reducing adverse drug events. 8,10 These advantages, however, do not come without associated risks of legal liability pointed out by physician making clinical diagnosis, 12 risks of alert fatigue, and negative impact on user skills by reliance on alert system, as well as limitation of identifying appropriate alerts.…”
Section: Background and Significancementioning
confidence: 99%
“…[7][8][9][10] The utilization of CDS has demonstrated different advantages for improving practitioner performance and clinical care, including prevention of harmful prescriptions 11 and reducing adverse drug events. 8,10 These advantages, however, do not come without associated risks of legal liability pointed out by physician making clinical diagnosis, 12 risks of alert fatigue, and negative impact on user skills by reliance on alert system, as well as limitation of identifying appropriate alerts. 13,14 Drug alerts are triggered when a medical order is incompatible with a set of parameters which may include dose ranges, frequency of administration, associated allergies, and medical conditions, among others.…”
Section: Background and Significancementioning
confidence: 99%